2018
DOI: 10.1016/j.neuron.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Prospection, Perseverance, and Insight in Sequential Behavior

Abstract: SummaryReal-world decisions have benefits occurring only later and dependent on additional decisions taken in the interim. We investigated this in a novel decision-making task in humans (n = 76) while measuring brain activity with fMRI (n = 24). Modeling revealed that participants computed the prospective value of decisions: they planned their future behavior taking into account how their decisions might affect which states they would encounter and how they themselves might respond in these states. They consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 56 publications
(78 reference statements)
2
76
0
Order By: Relevance
“…This model allows us to generate results that provide novel insight into the role of dACC in cognition. First, our results emphasize the core role of dACC in prediction, a role that is central to other theories, albeit not ones that directly involve pursuit 11, 17, 20, 21, 47, 48 . One recent study is particularly relevant to these results 20 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This model allows us to generate results that provide novel insight into the role of dACC in cognition. First, our results emphasize the core role of dACC in prediction, a role that is central to other theories, albeit not ones that directly involve pursuit 11, 17, 20, 21, 47, 48 . One recent study is particularly relevant to these results 20 .…”
Section: Discussionsupporting
confidence: 53%
“…Based on its role as a nexus for motivational, cognitive, and motor information 18, 23 , and its demonstrated role in human prospection 11, 25 , we hypothesized that dACC would be critical for predictive pursuit (Figure 3A). We fit a statistically unbiased Linear-Nonlinear Generalized Linear model (GLM 2628 ) to responses of 150 well-isolated dACC neurons (K: n=31; H: n=119).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More broadly our results are in accordance with a view that decision-making is not accomplished by any single area in isolation but by multiple areas such as the mOFC/vmPFC and the ACC on the basis of different criteria 42,43 . The ACC is especially concerned with signaling the value of behavioral change and alternative courses of action 7,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…To address this question, we recorded in the midcingulate cortex (MCC) and lateral prefrontal cortex (LPFC), because these two frontal areas both display particularly long spiking timescales and are functionally implicated in cognitive processes operating over extended timescales. These interconnected regions collaborate in monitoring performance and in integrating the history of outcomes for flexible decisions (Kennerley et al, 2006;Khamassi et al, 2015;Kolling et al, 2018;Medalla and Barbas, 2009;Rothe et al, 2011;Seo and Lee, 2007;Womelsdorf et al, 2014a). Recent anatomical and physiological investigations revealed that the cingulate region has relatively higher levels of synaptic inhibition on pyramidal neurons than LPFC, with higher frequency and longer duration of inhibitory synaptic currents (Medalla et al, 2017), suggesting that excitatory and inhibitory cell types differentially contribute to the specific dynamics of distinct frontal areas.…”
Section: Introductionmentioning
confidence: 99%